Alternative Techniques for Developing Real Estate Price Indexes - Palmquist, Raymond B. (The Review of Economics and Statistics, 1980)
T HE rapid rate of increase in the prices of houses in recent years has resulted in renewed interest in trends in residential real estate. A widely quoted study by the Harvard-MIT Joint Center for Urban Studies (Solomon, et al., 1977) showed that in 1976 only 27% of families could afford to buy the median priced new home, a significant change from 1970 when 46% of families were able to make such a purchase. Such rapid changes could result in significant income redistribution effects, and policy proposals have been numerous. To assess these trends and proposals, it is necessary to have accurate methods of developing residential real estate price indexes. Most real estate indexes have been based on the average or median selling price in each year for new or used houses. Yet there may exist substantial differences in the houses on the market at different times, so such indexes contain quality changes as well as pure price changes. Because housing is a highly heterogeneous commodity, the measurement of quality-adjusted price changes has proven difficult. Such measurement is desirable not simply because of the recent significant price changes in the real estate market, but also because economists have found property values to be one of the best sources of information on goods for which markets do not exist. Although in the past cross-sectional studies have generally been used for this purpose, questions remain concerning the timing of the impacts. Comparisons of real estate price indexes can provide insights into the dynamics of such effects. Among the techniques suggested for developing quality-adjusted price indexes, approaches using hedonic regressions and repeat-sale regressions appear to be the most promising. In this paper, alternative local price indexes are developed using modifications of the hedonic and repeat-sale techniques. For the case considered, the two independent techniques provide statistically identical indexes of the real price of housing. The estimated rate of increase in house prices using the hedonic and repeat-sale techniques is substantially lower than the non-quality adjusted rate implied by the change in average selling price.